Pengesahan Perkawinan Sebagai Administrasi Pemberantasan Keterbelakangan Pendidikan - Erni Dwita Silambi; Rudini Hasyim Rado; M. Saiful Fahmi (BADAN PENERBIT STIEPARI PRESS, 2023)
In the Malind Anim community in Buti, many couples only marry based on customary law, so they do not yet have a marriage certificate. The aim of this community service is to provide understanding to the community about the importance of registering marriages and also to facilitate people who have not legally married to be registered and to carry out marriages in churches and civil registries. The implementation method is carried out in 3 stages, namely starting from data collection, counseling about the importance of legalizing marriage as an administration for eradicating educational backwardness and implementing mass weddings. The result of this service was that 24 couples had entered into religious and legal marriages and 24 of these couples had religious marriage certificates and also marriage certificates from the Merauke Regency Government, namely the Civil and Population Registry Office.